The Socio-economic Impacts of Framework Programmes in Transition Countries - A systemic Approach of Assessment Methods - Attila Havas; Lajos Nyiri (Hungarian Academy of Sciences, Institute of Economics, 2004)
This paper assesses the socio-economic impacts stemming from Research,Technological Development and Demonstration Framework Programmes (FPs) project participation in a transition economy. Some of the most significant impacts of Central and Eastern European participation in FPs can only be understood in the context of the changing national innovation systems (NIS). In other words, when assessing impacts, besides the usual questions on product and process development, job creation, etc., a broader set of questions should be asked, concerning competences: managerial, project development, network and collaboration-building capabilities, i.e. the process, and elements, of organisational learning, broadly defined. Our main methodological argument is based on two underlying characteristics of the Hungarian NIS. First, it had been fragmented during the planned economy the academy-industry relations had been rather weak. Second, due to the overall socio-economic transition it is also in flux, some former links have been further damaged, while new players have appeared and new, stronger incentives have been put in place to form new partnerships. Behavioural and organisational effects of FP participation are likely to be crucial besides the usual outputs and impacts. Our main policy conclusion is that it would well worth the effort to apply a broader framework for impacts and effects to a larger, statistically representative sample. Thus a reliable description could be obtained, on which basis sound policy conclusions could also be drawn.
Keywords: 330